El triunfo de la moneda dinástica en el Imperio Bizantino. Isaurios, Amorianos y Macedonios - Francisco Olmos, José María de (Documenta & Instrumenta - Documenta et Instrumenta, 2010)
The problem of succession to the throne in the Byzantine Empire the 8th til 11th centuries is examined. The dynastic idea as opposed to providential succession is increasingly appreciated with greater clarity, though the latter never came to disappear. In the Isaurian coins up to five members of the imperial family are seen in the types, a kind of iconographical genealogy. The Amorians try to solve the problem of male succession promoting the daughters of the imperial couple. Even-tually we will see the dynastic triumph with the Macedonians, where many usupers ruled, though they were always linked to the royal family either through marriage or adoption, being the end of the dynasty an example of fidelity, as a woman as such could govern on her own.
Keywords: Byzance; Succession to the throne; VIII-XI Century; Isaurians; Amorians; Macedonians; Dinastic coins